2016
DOI: 10.1371/journal.pone.0154688
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibodies with Amylase Activity from Cerebrospinal Fluid and Serum of Patients with Multiple Sclerosis

Abstract: We have recently shown that IgGs from serum and cerebrospinal fluid (CSF) of MS patients are active in hydrolysis of DNA and myelin basic protein. According to literature data, anti-DNA and anti-MBP abzymes may promote important neuropathologic mechanisms in this chronic inflammatory disorder and in MS pathogenesis development. At the same time, the involvement of antibodies with amylase activity in the pathogenesis of any autoimmune disease has not yet been identified. Electrophoretically and immunologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…As demonstrated before, the method of isolation of IgGs developed by us excludes contamination with classical enzymes . Based on several very strict criteria developed previously, we have reliably proven that DNase‐, MOG‐, MBP‐hydrolysing activities are intrinsic properties of IgG abzymes from the plasma of spontaneously diseased MOG and DNA‐met‐BSA treated C57BL/6 mice, and they are not because of co‐purified canonical DNases or proteases .…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…As demonstrated before, the method of isolation of IgGs developed by us excludes contamination with classical enzymes . Based on several very strict criteria developed previously, we have reliably proven that DNase‐, MOG‐, MBP‐hydrolysing activities are intrinsic properties of IgG abzymes from the plasma of spontaneously diseased MOG and DNA‐met‐BSA treated C57BL/6 mice, and they are not because of co‐purified canonical DNases or proteases .…”
Section: Resultsmentioning
confidence: 60%
“…To protect Abs from viral and bacterial contamination, they were filtered through syringe‐driven filter units (Millex; 0.1 μm) and kept in sterilized tubes. The absence of viral and bacterial colonies in Ab preparations was checked as shown previously . SDS‐PAGE analysis proving electrophoretic homogeneity of IgGs under non‐reducing conditions (0.1%) was performed in 4‐15% gradient gels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that IgGs from sera and cerebrospinal fluid of MS patients are active in the hydrolysis of DNA, MBP, and oligosaccharides. In addition, the specific RAs of these abzymes from the CSF of MS patients are dependently on their different activities were approximately 30-to 60-fold higher comparing to serum Abzs from the same patients [67][68][69]. It means that during spontaneous or induced development of ADs as a result of specific differentiation of lymphocytes in cerebrospinal fluid there may be formation of cells producing different catalytic antibodies directly in cerebrospinal fluid.…”
Section: Lymphocyte Proliferation In Sle Prone Micementioning
confidence: 92%
“…In this regard, data comparing relative Abz activities from serum and cerebrospinal fluid (CSF) of the same MS patients with multiple sclerosis should be noted [67][68][69]. It was shown that IgGs from sera and cerebrospinal fluid of MS patients are active in the hydrolysis of DNA, MBP, and oligosaccharides.…”
Section: Lymphocyte Proliferation In Sle Prone Micementioning
confidence: 99%